Education of Posyandu Cadres on The Hazards of Diarrhea in Toddlers in Desa Ciampea Udik, Kecamatan Ciampea, Kabupaten Bogor - Fadhilla, Reza; Nadiyah, Nadiyah; Utami, Dessy Aryanti; Marsidi, Sitti Rahmah; Muslim, Siti Zaqiah; Durotunisa, Siti Irma; Teftae, Ester Tyo Fany; Nuryanah, Witri; Apraningrum, Anisa Elok; Hanifah, Luthfi Nur (Jurnal Kreativitas Pengabdian Kepada Masyarakat (PKM), 2025)
ABSTRACT Diarrhea is defined as a phase of abnormal feces discharge in the form of more liquid consistency with a frequency of more than 3 times a day. Pathogens that cause diarrhea are infections of Vibrio cholerae, Shigella, Campylobacter jejuni, Escherichia coli, and Salmonella. For toddlers, diarrhea can cause death if not treated properly because they are easily dehydrated. Therefore, one step to overcome diarrhea in toddlers is to increase the capacity of cadres. This community service activity aims to educate posyandu cadres about the hazards of diarrhea in toddlers in the Desa Ciampea Udik, Kecamatan Ciampea, and Kabupaten Bogor. A total of 36 cadres who participated in the activity were educated and evaluated by providing pre-test and post-test questions. The test results showed that the average pre-test score was 69.7, and the average post-test score increased to 74.9. In the future, activities that need to be carried out include educating posyandu cadres about the use and processing of local food in an effort to increase toddler immunity, especially against the risk of diarrhea. Keywords: Diarrhea, Education, Posyandu cadres, Toddlers